2018
DOI: 10.1002/jcb.28298
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‐183 improve myocardial damager via NF‐kb pathway: In vitro and in vivo study

Abstract: Aim: The aim of this study is to evaluate the effects of microRNA-183 (miRNA-183) in myocardial damager.Methods: In the cell experiment, the H9C2 cell was divided into three groups: NC group, Model group, and miRNA group. The cell apoptosis and relative proteins' expressions were measured by flow cytometry and Western blot assay. The in vivo study of the rats was divided into three groups: Sham group, Model group, and miRNA group. The pathology, Infarct size, cell apoptosis, and relative protein expressions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…Many reports illustrated that many miRNAs have effects on NF‐κB pathway . According to Xing et al, miRNA‐183 could improve myocardial damage via NF‐κB signaling . Thus far, previous study has confirmed that upregulation of miR‐27 suppressed the pathogenesis of osteoarthritis by inactivating the NF‐κB pathway .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Many reports illustrated that many miRNAs have effects on NF‐κB pathway . According to Xing et al, miRNA‐183 could improve myocardial damage via NF‐κB signaling . Thus far, previous study has confirmed that upregulation of miR‐27 suppressed the pathogenesis of osteoarthritis by inactivating the NF‐κB pathway .…”
Section: Discussionmentioning
confidence: 96%
“…32,33 According to Xing et al, miRNA-183 could improve myocardial damage via NF-κB signaling. 34 Thus far, previous study has confirmed that upregulation of miR-27 suppressed the pathogenesis of osteoarthritis by inactivating the NF-κB pathway. 35 It has found that IL-6 and TNF-α are important target genes in NF-κB signaling pathway.…”
Section: Downregulated Expression Of Mir-27 In Myocardial Ischemia mentioning
confidence: 87%
“…Several studies have shown that many miRNAs have effects on the NF‐κB pathway . A previous study confirmed that miRNA‐183 could relieve myocardial damage via the NF‐κB pathway . It has been shown that the upregulation of gga‐miR‐16‐5p repressed the proliferation of mycoplasma gallisepticum‐infected fibroblast cells by PI3K/Akt/NF‐κB inactivation .…”
Section: Discussionmentioning
confidence: 99%
“… 33 The miRNAs −20, 22 , 29 −30, 34 −410, 35 −515, 34 −134, 23 −183 36 , 37 met all these characteristics. 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54…”
Section: Introductionmentioning
confidence: 99%